2009
DOI: 10.1194/jlr.m800555-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic, cytoplasmic triacylglycerol pool in enterocytes revealed by ex vivo and in vivo coherent anti-Stokes Raman scattering imaging

Abstract: The absorptive cells of the small intestine, enterocytes, are not generally thought of as a cell type that stores triacylglycerols (TGs) in cytoplasmic lipid droplets (LDs). We revisit TG metabolism in enterocytes by ex vivo and in vivo coherent anti-Stokes Raman scattering (CARS) imaging of small intestine of mice during dietary fat absorption (DFA). We directly visualized the presence of LDs in enterocytes. We determined lipid amount and quantified LD number and size as a function of intestinal location and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
140
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 53 publications
5
140
0
Order By: Relevance
“…The same group also used CARS to investigate nanoparticle environmental pollutants in water and their localization in fish tissue see Figure 23(e) [233]. Dietery fat absorbtion was studied by Zhu et al who used CARS imaging of cytoplasmic lipid droplet dynamics and metabolism in mice intestinal tissue models [234]. Wang et al used CARS combined with SHG and TPEF to image various grades of atherosclerotic lipid lesions in porcine arteries, as seen in Figure 23(c) [235].…”
Section: Applicationsmentioning
confidence: 99%
“…The same group also used CARS to investigate nanoparticle environmental pollutants in water and their localization in fish tissue see Figure 23(e) [233]. Dietery fat absorbtion was studied by Zhu et al who used CARS imaging of cytoplasmic lipid droplet dynamics and metabolism in mice intestinal tissue models [234]. Wang et al used CARS combined with SHG and TPEF to image various grades of atherosclerotic lipid lesions in porcine arteries, as seen in Figure 23(c) [235].…”
Section: Applicationsmentioning
confidence: 99%
“…As the amount of dietary fat increases, postprandial triglyceridemia also increases ( 3,4 ). In addition, under HF dietary challenges, TG is also found packaged in enterocytes in cytoplasmic lipid droplets (CLDs) ( 5 ). We recently demonstrated that this storage pool of TG in enterocytes expands and depletes relative to the fed-fasted state and is present whether mice are acutely or chronically challenged by high levels of dietary fat ( 5 ).…”
mentioning
confidence: 99%
“…In addition, under HF dietary challenges, TG is also found packaged in enterocytes in cytoplasmic lipid droplets (CLDs) ( 5 ). We recently demonstrated that this storage pool of TG in enterocytes expands and depletes relative to the fed-fasted state and is present whether mice are acutely or chronically challenged by high levels of dietary fat ( 5 ). These results suggest that TG stored in CLDs are eventually hydrolyzed, reesterifi ed, and secreted on chylomicrons.…”
mentioning
confidence: 99%
“…Figure 3a shows fs SRL image of triacylglycerol pools stored in enterocytes of mouse small intestine [18] based on the signal from C--H stretch vibration. By comparing the C--H off-resonance images and the time off images obtained by TAMP and LIA, it was found that TAMP-based detection produced the same signal level as LIA based detection but reduced the noise by 3 time ( Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Small intestines were extracted from 3-month old male mouse (C57BL/6) as described previously [18]. For intact tissue imaging, ex vivo fresh tissue (5 mm long) from small intestine (S2, representing upper jejunum) was placed in 3 mL Dulbecco's Modified Eagle's Medium (Gibco, Carlsbad, CA) supplemented with 20 mM HEPES, 100 U/mL penicillin-streptomycin (Gibco), and 10% fetal bovine serum.…”
Section: Tissue Preparationmentioning
confidence: 99%